Low magnetic field induced strong magnetoelectric coupling in three phase composite films with ferroelectric domain switchability. Issue 10 (July 2020) - Kumar, Amit; Saini, Sandeep; Yadav, K.L.; Azam, Mohammad; Ahmed, Ishtiaq; Kumar, Sanjeet; Pandit, Triloki; Shankar, Uma; Singh, Satyendra
Abstract: We report the dielectric, ferroelectric, magnetic and magnetoelectric properties of three-phase composite thick films (thickness~0.25 mm) of BaFe12 O19 –poly(vinylidene-fluoride)–BaTiO3 (abbreviated as BaFBT60) and SrFe12 O19 –poly(vinylidene-fluoride)–BaTiO3 (abbreviated as SrFBT60). A very strong magnetoelectric voltage coefficient (α33 ) of about 60 mV/cmOe and 40 mV/cmOe was observed at a small magnetic field of 300 Oe for the BaFBT60 and SrFBT60 films, respectively. The nature of the zero field cooling as well as the field cooling curves of composite films was suggested as a spin-glass type behavior. A remarkable value of magnetocapacitance (MC) of about 7.2% was observed for BaFBT60 composite film. The switchability phenomena of the ferroelectric domains were observed in the presence of the magnetic field of about 700 Oe. In addition, very significant information about the domain wall mobility was obtained from the irreversible ( α ) and reversible (ϵre ) coefficients as calculated from the Rayleigh analysis.